2016
DOI: 10.1016/j.ibbai.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Correlación entre las medidas de centralidad de los países y el impacto de sus artículos. Caso de estudio de la investigación sobre biotecnología en Latinoamérica

Abstract: El objetivo del presente estudio es develar la estructura latente de la red latinoamericana de colaboración regional en la investigación sobre biotecnología y determinar si el impacto de los artículos latinoamericanos sobre biotecnología se relaciona con las medidas de centralidad (grado, intermediación y proximidad) de los países latinoamericanos en la estructura de la red de colaboración regional. Para lograrlo se examinaron 14 173 artículos, publicados entre 1988 y 2012, combinando técnicas del análisis de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In other words, the scientific collaboration continues to be lower than the rates of collaboration with the most productive central countries. A study about collaboration and scientific impact of Latin American countries in the area of biotechnology found that the increase in research in this sector originates from international collaboration, especially with the more developed countries, those occupying the influential positions in the area, such as the United States, Japan, Germany, England, Spain, and France [13]. The authors emphasize that, in a network of scientific collaboration, it is not only important to have a good production and impact but to have the capacity to become a mediator or link in establishing collaboration between the countries participating in the productive research network.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the scientific collaboration continues to be lower than the rates of collaboration with the most productive central countries. A study about collaboration and scientific impact of Latin American countries in the area of biotechnology found that the increase in research in this sector originates from international collaboration, especially with the more developed countries, those occupying the influential positions in the area, such as the United States, Japan, Germany, England, Spain, and France [13]. The authors emphasize that, in a network of scientific collaboration, it is not only important to have a good production and impact but to have the capacity to become a mediator or link in establishing collaboration between the countries participating in the productive research network.…”
Section: Introductionmentioning
confidence: 99%